The approach of Hospital Pedagogy in the Venezuelan context - Marian SERRADAS FONSECA (Ediciones Universidad de Salamanca, 2018)
This document is intended to represent the reality of Hospital Pedagogy in Venezuela. Its purpose is to provide a historical view first, of the most significant events that allowed the emergence, development and consolidation of Hospital Pedagogy in Venezuela, as well as the implementation and commissioning of the first hospital wards. Then, addressing teacher training in Hospital Pedagogy, he continues to research in the advancement of this type of education in our context, as well as the description of programs and projects conducted in the country for the benefit of the hospitalized population and the presentation of some final considerations.